The Romanticism of Alcoholic Beverage Regulation in Indonesia: Evidence of Legal Uncertainty? - Martin Roestamy; Adi Rahmanur Ibnu (Sriwijaya Law Review, 2022)
Legal provisions regarding alcoholic beverages are a complex issue in Indonesia. Therefore, this relates to several aspects, ranging from health or adverse and destructive impacts, halal and haram, to investment-related economic factors. However, to date, no law in Indonesia explicitly regulates alcoholic beverages. The formation of the existing Bill on Alcoholic Drinks must consider all aspects, whether social, cultural, economic, political, or religious. In addition, drafting the Alcoholic Drinks Bill must involve all elements of society comprehensively. This article aims to conduct a legal analysis of the legal policy of regulating alcoholic beverages in Indonesia. The analysis is carried out on the applicable positive law (ius constitutum) and legal policies to regulate alcoholic beverages in the future (ius constituendum). The Normative Legal Research Method is used to analyse the legal system of alcoholic beverages in Indonesia, which shows the uncertainty of management, control, and supervision. This impacts the conflict of interest between investment and the moral life of the Indonesian people. As a result, this study recommends that lawmakers reform the alcoholic beverage law in Indonesia by paying attention to Pancasila as the basis of the nation's philosophy. For this reason, integrated regulation and supervision of alcoholic beverages are needed, and law is urgently needed to unify the overlapping and diverse regulations regarding alcoholic beverages.